O desafio tecnológico da produção de VO2 por sputtering reativo: vantagens e limitações da técnica - Schneider, Angélica Daiane (2022)
The vanadium dioxide(VO2) presents a semiconductor-to-metal (SMT) transition near room temperature, as well as a structural phase transition (monoclinic-tetragonal or triclinictetragonal). The first report on SMT is from 60 years ago, but the underneath physics is still not completely clear. From the fundamental point of view, the current trend is to include the VO2 in the class of complex materials, where the interplay among several mechanisms determines the physical properties. Like other systems of this class, the behavior near transition is strongly related to the material stoichiometry and morphology, wich impacts its applications. On the other hand, the production of VO2 samples using sputtering in a large scale is attractive because of the work temperature of this system. In this work we explore the production of VO2 thin films on silicon substrates by reactive sputtering technique in order to establish its versatility and its reproduction limits. More than twenty samples were produced and used to evaluate the effects of metal target poisoning (by using XPS measuments and monitoring of the target impedance), as well as the atmosphere composition inside the chamber (by using a RGA) on the samples quality. The crystallographic and topographic characteristics of some samples produced under distinct parameters were also investigated. In order to analyze the sample surfaces the atomic force mycroscope was used. The crystallographic phases and its transitions were analyzed by X ray diffraction and from this measurements XR simulations and Williamsom-Hall (W-H) plot were performed to understand the role played by the strain in the film growth. They show that the system assumes crystallographic structures that describe a trajectory in the bulk VO2 phase diagram. Initial results on the electrical response with the current perpendicular to the substrate are shown. Such results were obtained with the CP-AFM technique in samples produced over metallic electrodes. Magnetic susceptibility measurements as a function of temperature and magnetization curves were performed and are presented, indicating promising paths to be explored.